Long-term monitoring of microsporidia, Cryptosporidium and Giardia infections in western Lowland Gorillas (Gorilla gorilla gorilla) at different stages of habituation in Dzanga Sangha Protected Areas, Central African Republic - Sak, Bohumil; Petrzelkova, Klara J; Kvetonova, Dana; Mynarova, Anna; Shutt, Kathryn A; Pomajbikova, Katerina; Kalousova, Barbora; Modry, David; Benavides, Julio; Todd, Angelique; Kvac, Martin (PloS one, 2013)
BACKGROUND: Infectious diseases pose one of the greatest threats to endangered species, and a risk of gastrointestinal parasite transmission from humans to wildlife has always been considered as a major concern of tourism. Increased anthropogenic impact on primate populations may result in general changes in communities of their parasites, and also in a direct exchange of parasites between humans and primates. AIMS: To evaluate the impact of close contact with humans on the occurrence of potentially zoonotic protists in great apes, we conducted a long-term monitoring of microsporidia, Cryptosporidium and Giardia infections in western lowland gorillas at different stages of the habituation process, humans, and other wildlife in Dzanga-Sangha Protected Areas in the Central African Republic. RESULTS: We detected Encephalitozoon cuniculi genotypes I and II (7.5%), Enterocytozoon bieneusi genotype D and three novel genotypes (gorilla 1-3) (4.0%), Giardia intestinalis subgroup A II (2.0%) and Cryptosporidium bovis (0.5%) in gorillas, whereas in humans we found only G. intestinalis subgroup A II (2.1%). In other wild and domestic animals we recorded E. cuniculi genotypes I and II (2.1%), G. intestinalis assemblage E (0.5%) and C. muris TS03 (0.5%). CONCLUSION: Due to the non-specificity of E. cuniculi genotypes we conclude that detection of the exact source of E. cuniculi infection is problematic. As Giardia intestinalis was recorded primarily in gorilla groups with closer human contact, we suggest that human-gorilla transmission has occurred. We call attention to a potentially negative impact of habituation on selected pathogens which might occur as a result of the more frequent presence of humans in the vicinity of both gorillas under habituation and habituated gorillas, rather than as a consequence of the close contact with humans, which might be a more traditional assumption. We encourage to observe the sections concerning hygiene from the IUCN best practice guidelines for all sites where increased human-gorilla contact occurs.
Keywords: Enterocytozoon; Zoonoses; Feces; Středoafrická republika; Genotype; fylogeneze; kryptosporidióza; Sequence Analysis, DNA; Central African Republic; Cryptosporidiosis; Phylogeny; sekvenční analýza DNA; molekulární sekvence - údaje; zoonózy; Gorilla gorilla; nemoci lidoopů; Social Environment; Time Factors; Ape Diseases; Animals; Microsporidiosis; Encephalitozoon cuniculi; lidé; giardiáza; Humans; zvířata; Giardia; habituace (psychofyziologie); časové faktory; mikrosporidióza; Cryptosporidium; genotyp; Microsporidia; Giardiasis; Molecular Sequence Data; sociální prostředí; Habituation, Psychophysiologic; feces